2019
DOI: 10.1021/acs.iecr.9b00686
|View full text |Cite
|
Sign up to set email alerts
|

Porous Fe Hollow Structures with Optimized Impedance Matching as Highly Efficient, Ultrathin, and Lightweight Electromagnetic Wave Absorbers

Abstract: Porous Fe hollow nanospheres (HNs) were fabricated successfully through hydrogen thermal reduction on solvothermal synthesized Fe 3 O 4 HNs. The electromagnetic wave (EMW) absorption performances of the porous Fe 3 O 4 and Fe HNs were investigated in 2.0−18.0 GHz. Owing to an optimized matching from the modulated permittivity and increased permeability, the porous Fe HNs exhibited remarkably enhanced EMW absorption than porous Fe 3 O 4 HNs as well as previously reported Fe-based absorbers. The minimum reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…With the widespread use of electronic devices and wireless communication, electromagnetic interference has become a serious problem in polluting the communication environment and harming human health [1][2][3]. To tackle the adverse problems we are facing, high-performance microwave absorbers are urgently demanded, which can convert most of the electromagnetic energy onto the surface into thermal or other forms of energy [4,5]. By and large, high-efficiency microwave absorbers are required to fulfill the four characteristics of wide bandwidth, strong absorption, low thickness as well as light mass.…”
Section: Introductionmentioning
confidence: 99%
“…With the widespread use of electronic devices and wireless communication, electromagnetic interference has become a serious problem in polluting the communication environment and harming human health [1][2][3]. To tackle the adverse problems we are facing, high-performance microwave absorbers are urgently demanded, which can convert most of the electromagnetic energy onto the surface into thermal or other forms of energy [4,5]. By and large, high-efficiency microwave absorbers are required to fulfill the four characteristics of wide bandwidth, strong absorption, low thickness as well as light mass.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the impedance matching level and overall performance, ZnO was usually integrated with magnetic materials especially ferromagnetic metals/alloys owing to their larger saturation magnetization and higher Snoek's limit. [ 7,8 ] For instance, flower‐like ZnO@Ni, [ 8 ] porous FeCo/ZnO nanosheets, [ 9 ] Fe@ZnO nanocapsules [ 10 ] were reported to exhibit outstanding EM wave absorption properties. However, to the best of our knowledge, there are very few reports about the microwave absorption performance of 1D ZnO‐magnetic metal/alloy composite nanostructures so far.…”
Section: Introductionmentioning
confidence: 99%
“…However, electromagnetic radiation produced in the use of electronic products cannot be underestimated for its harm brought to people’s living environment. , Due to the electromagnetic wave absorption materials (EWAMs), human beings are protected away from electromagnetic radiation, and electronic devices effectively alleviated other electromagnetic interference (EMI) by absorbing the disturbed electromagnetic waves or eliminating them through interference. Up to now, ferrite, metal powder, silicon carbide, and conductive fibers usually serve as traditional EWAMs, which are limited by their high density or narrow absorption band. Nanomaterials, polycrystalline iron fibers, and conductive polymers have received tremendous attention due to their superiority in the aspects of thickness, weight, and mechanical properties, which have great potentials in EWAMs. Among these materials, graphene is expected to be one of the most promising candidates for EWAMs for its unique two-dimensional structure, outstanding electrical properties, and high specific surface area. Wang et al have demonstrated the synthesis of GO/CNT-Fe 3 O 4 /NP, whose grain size is among 6–18 nm, and the maximum reflection loss is −38 dB with a broad band of about 16 GHz (<10 dB). Li et al have synthesized N-doped graphene nanosheets decorated by smaller-size superparamagnetic Fe 3 O 4 nanoparticles, which achieved the minimal reflection value of −65.3 dB at a thickness of 3.4 mm.…”
Section: Introductionmentioning
confidence: 99%